1984
DOI: 10.1111/j.1442-9993.1984.tb01359.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of invertebrates on foliage in forests of south‐eastern Australia

Abstract: Nearly 1500 foliage samples were collected from a total of 156 plant species, distributed at 16 study sites representing a wide range of forests and woodlands in south-eastern Australia. Samples were collected in all months. Invertebrates present in samples were counted, sorted into 13 categories, and the number present (> 3 mm in length) converted into density estimates. Densities of all invertebrates combined and invertebrate diversity were also calculated. Despite high variability there were some obvious di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 62 publications
5
79
1
Order By: Relevance
“…Similar results have been reported in other natural mature forest types (Lähde and Laiho, 1992;Halpern and Spies, 1995;Bengtsson et al, 2000;Crow et al, 2002;Wilson and McComb, 2005). In natural forests, structural and compositional heterogeneity contribute to high biological diversity (Woinarski and Cullen, 1984;Schoonmaker and McKee, 1988;Traill, 1993;Tyrrell and Crow, 1994;Tanabe et al, 2001;Keeton, 2006;Fischer et al, 2007). A diverse oak mature forest with diverse habitat components is likely to be related with high species diversity.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar results have been reported in other natural mature forest types (Lähde and Laiho, 1992;Halpern and Spies, 1995;Bengtsson et al, 2000;Crow et al, 2002;Wilson and McComb, 2005). In natural forests, structural and compositional heterogeneity contribute to high biological diversity (Woinarski and Cullen, 1984;Schoonmaker and McKee, 1988;Traill, 1993;Tyrrell and Crow, 1994;Tanabe et al, 2001;Keeton, 2006;Fischer et al, 2007). A diverse oak mature forest with diverse habitat components is likely to be related with high species diversity.…”
Section: Discussionsupporting
confidence: 77%
“…A diverse oak mature forest with diverse habitat components is likely to be related with high species diversity. Different attributes provided by various tree species such as diverse foliage, bark types, dead wood and coarse debris, and hollow bearing trees for nesting and shelter have been identified as important resource bases for different life forms (Recher, 1969;Woinarski and Cullen, 1984;MacNally et al, 2001;Franklin et al, 2002;Harvey et al, 2002;Mitchell et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Most arachnid species are sensitive to green, while a few taxa are sensitive to blue and red wavelengths (Dahl and Granda, 1989;Peaslee and Wilson, 1989;Zurek et al, 2015). Combined, the visual system of potential arachnid predators, and fewer arachnids on Eucalypts (Woinarski and Cullen, 1984) may result in low selection pressure from arachnid predators, explaining why beetles feeding on Eucalyptus can evolve different blue patterns from their background.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the stand structural complexity (sensu Lindenmayer and Franklin, 2002) added by Acacia spp. is a valuable foraging substrate for wildlife in montane ash forests because it has many species of invertebrates associated with it (Woinarski and Cullen, 1984) and provides places to nest (Beruldsen, 2003). MacArthur and MacArthur (1961) showed that bird species richness increases with increased vertical heterogeneity (Recher, 1969).…”
Section: Speciesmentioning
confidence: 99%